TEORI LABELLING DAN PENGARUHNYA TERHADAP KEDUDUKAN MANTAN NARAPIDANA DALAM BERMASYARAKAT - Dr. Fauzan Alfikri; Rama Rama Saputra (VERITAS, 2018)
Crime is perceived to affect Culture in Indonesia, the number of crimes will worsenthe image of Indonesia in the eyes of the world, and eventually Indonesia will beknown as the country with the highest crime rate. This is certainly not anachievement for a democratic unitary state, so the need to eradicate every crimeand to seek the cause of the occurrence of a crime, because one commits a crime,until the reason for the crime occurs, so the role and function of the CriminologyScience. This study uses the Juridical Empirical approach, which is a study thatemphasizes the real life of the community in Karawang regency, so any researchthat based or conceptualize the law as behavior or behavior and community actioncan be referred to as social research (law), empirical or research the nondoctrinal.Plunge directly in the life of the community, making observations andinterviews is one of the techniques taken in collecting any data required. One of thestudies that became the center of his research is Labeling Theory which is part ofthe supporting theories of Criminology. Labeling itself is a theory that studiesabout the reaction of a label attached to a thing or living creature. A person whocan not accept the label attached to him will most probably do abnormal actions,such as violence or even criminal crimes. Not infrequently the element of labelingis the reason for the repetition of a criminal act (Residivist).